Differentiating among pragmatic uses of words through timed sensicality judgments - Bambini, Valentina; Ghio, Marta; Moro, Andrea; Schumacher, Petra B. (Frontiers in Psychology, 2013)
Pragmatic and cognitive accounts of figurative language posit a difference between metaphor and metonymy in terms of underlying conceptual operations. Recently, other pragmatic uses of words have been accounted for in the Relevance Theory framework, such as approximation, described in terms of conceptual adjustment that varies in degree and direction with respect to the case of metaphor. Despite the theoretical distinctions, there is very poor experimental evidence addressing the metaphor/metonymy distinction, and none concerning approximation. Here we used meticulously built materials to investigate the interpretation mechanisms of these three phenomena through timed sensicality judgments. Results revealed that interpreting metaphors and approximations differs from literal interpretation both in accuracy and reaction times, with higher difficulty and costs for metaphors than for approximations. This suggests similar albeit gradual interpretative costs, in line with the latest account of Relevance Theory. Metonymy, on the contrary, almost equates literal comprehension and calls for a theoretical distinction from metaphor. Overall, this work represents a first attempt to provide an empirical basis for a theory-sound and psychologically-grounded taxonomy of figurative and loose uses of language.